Cheetahs and wild dogs show contrasting patterns of suppression by lions. (13th May 2014) - Swanson, Alexandra; Caro, Tim; Davies‐Mostert, Harriet; Mills, Michael G. L.; Macdonald, David W.; Borner, Markus; Masenga, Emmanuel; Packer, Craig; Boutin, Stan
Summary Top predators can dramatically suppress populations of smaller predators, with cascading effects throughout communities, and this pressure is often unquestioningly accepted as a constraint on mesopredator populations. In this study, we reassess whether African lions suppress populations of cheetahs and African wild dogs and examine possible mechanisms for coexistence between these species. Using long‐term records from Serengeti National Park, we tested 30 years of population data for evidence of mesopredator suppression, and we examined six years of concurrent radio‐telemetry data for evidence of large‐scale spatial displacement. The Serengeti lion population nearly tripled between 1966 and 1998; during this time, wild dogs declined but cheetah numbers remained largely unchanged. Prior to their local extinction, wild dogs primarily occupied low lion density areas and apparently abandoned the long‐term study area as the lion population 'saturated' the region. In contrast, cheetahs mostly utilized areas of high lion density, and the stability of the cheetah population indicates that neither high levels of lion‐inflicted mortality nor behavioural avoidance inflict sufficient demographic consequences to translate into population‐level effects. Population data from fenced reserves in southern Africa revealed a similar contrast between wild dogs and cheetahs in their ability to coexist with lions. These findings demonstrate differential responses of subordinate species within the same guild and challenge a widespread perception that lions undermine cheetah conservation efforts. Paired with several recent studies that document fine‐scale lion‐avoidance by cheetahs, this study further highlights fine‐scale spatial avoidance as a possible mechanism for mitigating mesopredator suppression.